AI as a creative partner: a PRISMA review of AI’s role in supporting creativity in education - Urmeneta, Alex; Romero, Margarida (Frontiers in Education, 2025)
Creativity is considered an important competency for personal and professional development in the current society. With the integration of artificial intelligence (AI) in education, there is increasing interest in understanding how AI can support the creative process and how its usage in various contexts might affect user agency. Nevertheless, the specific role of AI in the support to the creative process is not clearly identified in the literature. To address this gap, a comprehensive PRISMA review of the existing research explored the different contexts and use cases for AI in support of creativity, identifying 20 articles from the ScienceDirect database after a systematic review of 111 research papers. The 20 selected papers identified 5 primary use cases for AI in support of creativity in educational settings including academic achievement, chatbots, diagnostics and evaluation, and literature reviews and frameworks. Of these use cases, the most common applications of AI tend to occupy a more passive role where it supports brainstorming, creative writing, and adaptive learning systems. In these instances, user agency is considered high as the user is actively leading the process. In situations where AI functions as a co-collaborator, human agency is reduced as AI takes on a more substantial role in the creative process. Domain and context also play a role in how AI is currently supporting creativity in educational settings. Generic domains support divergent thinking while more specific domains may reduce creative possibilities, but provide more structured support in the creative process.